Effect of using bolus on the efficiency of the 3DCRT of the breast cancer after mastectomy - Iman Ghali Hassan,; Nabaa Abdulateef Rasheed Naji,; Hadeel Kamil Abdullah, (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the effect of using bolus on the efficiency of three-diensional conformation radiation treatment of breast cancer post-mastectomy. Method: The prospective, clinical study was conducted at Al-Amal Center for Radiation Therapy and Nuclear Medicine, Iraq, from November 2020 to April 2021, and comprised patients with synchronous bilateral breast cancer with regional lymph nodes who underwent mastectomy. The three-diensional conformation radiation treatment technique was used to evaluate the dose received by the planning target volume and the organs at risk. The plans were generated using a treatment planning system, the plans were then fed into a linear accelerator. The plans had one isocenter for both breasts to avoid the errors that may cause the overlapping of the radiation fields with and without the use of bolus. Data was analysed using SPSS 24. Results: There were 23 female patients with mean age 49.28±8.79 years (range: 35-62 years). There were 7(30.4%) females residing in rural areas, while 16(69.6%) lived in urban areas. The use of bolus increased the radiation dose coverage percentage of the planning target volume of the right (p=0.0002) and left (p=0.0164) breasts, while the right (p=0.3977) and left (p=0.7940) supraclavicular nodes were not significantly covered by the radiotherapy dose. The use of bolus showed a strong significant decrease of the mean dose that was received by the left lung (p=0.00001). Also, the use of bolus caused significant reduction in the amount of the mean scattered dose that reached the heart (p=0.00001) and larynx (p=0.00004). Conclusion: The use of bolus provided a complete radiotherapy dose coverage for the right and left breasts, as well as an excellent protection for the left lung, hear and larynex. Key Words: Mastectomy, Breast, Nuclear, Lung, Lymph Nodes, Radiation, Larynx